2008
DOI: 10.1007/s00198-008-0611-5
|View full text |Cite
|
Sign up to set email alerts
|

Weight-bearing bones are more sensitive to physical exercise in boys than in girls during pre- and early puberty: a cross-sectional study

Abstract: Summary We carried out a cross-section study of the sexspecific relationship between bone mineral content and physical activity at sites with different loading in pre-and early pubertal girls and boys. There was significant sensitivity of bone mineral content of the hip to physical exercise in boys, but not in girls. Background Since little is known whether there are sex differences in sensitivity of bone to loading, we investigated sex differences in the cross-sectional association between measures of physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 43 publications
6
53
0
10
Order By: Relevance
“…Until now, the most of study were focused on BMD of elite players in side-to-side effects, but a few investigations have been performed for normal people [30,31]. In this study, we observed that the non-dominant hand BMD of moderate and low physical activity groups were significantly lower than those in dominant hand, but did not in high activity group.…”
Section: Bmd In the Forearmmentioning
confidence: 54%
“…Until now, the most of study were focused on BMD of elite players in side-to-side effects, but a few investigations have been performed for normal people [30,31]. In this study, we observed that the non-dominant hand BMD of moderate and low physical activity groups were significantly lower than those in dominant hand, but did not in high activity group.…”
Section: Bmd In the Forearmmentioning
confidence: 54%
“…The magnitude of benefit in terms of bone strength will depend on the nature of the structural change, and possibly on the gender. Indeed, increasing levels of physical activity were associated with higher response weight-bearing BMD in boys than in girls before puberty (60). An effect consisting primarily of an increased periosteal apposition and consecutive diameter will confer greater mechanical resistance than a response limited to the endosteal apposition rate leading essentially to a reduction in the endocortical diameter.…”
Section: Physical Activitymentioning
confidence: 99%
“…Studien, die Kinder vor und zu Beginn der Pubertät einschlossen, zeigten, dass die KF durch MVPA und Sportprogramme vor der Pubertät stärker beeinflusst wurde als zu Beginn der Pubertät [11,12,30,43,44,45]. Besonders bei prä-pubertären Jungen wurde in einigen Beobachtungs-und Interventionsstudien ein bedeutender osteogener Effekt von KA und Sport beobachtet [10,11,45,46].…”
Section: Tab 4 Interventionsstudien (Rct Ct) Zum Einfluss Von Körpeunclassified
“…Besonders bei prä-pubertären Jungen wurde in einigen Beobachtungs-und Interventionsstudien ein bedeutender osteogener Effekt von KA und Sport beobachtet [10,11,45,46]. Dieser Effekt lässt sich durch eine stärke-re Beziehung zwischen KA und KF sowie durch die höhere KA/MVPA und Muskelstärke bei Jungen erklären [10,11,41,42,47].…”
Section: Tab 4 Interventionsstudien (Rct Ct) Zum Einfluss Von Körpeunclassified
See 1 more Smart Citation